Correlation of Biochemical Parameters with Cytomorphological grading in Hashimoto’s Thyroiditis - Sharma, Amrita Dhakal; N, Navya B; Alva, Sathyavathi R (Annals of Pathology and Laboratory Medicine, 2019)
Background: Hashimoto’s thyroiditis (HT) is one of the most common cause of hypothyroidism in iodine sufficient areas. Diagnosis of HT is based on clinical, cytomorphological and biochemical parameters. Fine Needle Aspiration Cytology (FNAC) of thyroid provides a safe and accurate method for diagnosis of HT. Cytological grading of HT helps in assessing the severity of the disease and can predict the thyroid functional status. Methods: Retrospectively, 50 diagnosed cases of HT on FNAC were studied over a period of 6 months in a tertiary care hospital. Clinical, biochemical parameters such as T3, T4 and TSH values were collected. Cytological grading of FNAC smears was done based on Bhatia et al cytological grading system into three grades. These grades were compared with the clinical and biochemical parameters of HT. Result: Of 50 patients, 47 were females. Maximum number of cases were seen between 36 -45 years. Most of the patients presented with goiter. 31 out of 50 (62%) cases were grade II thyroiditis, of them most cases were hypothyroid. 17 out of 50 cases (34%) were grade I thyroiditis, of which most cases were euthyroid biochemically. Conclusion: Higher the grades of HT in cytology the more abnormal are the biochemical parameters. A combined approach of cytological grading along with clinical and biochemical parameters can detect subclinical hypothyroid state which provides a guide to therapy.